Beautiful wing coloration pattern in a new doratomantispine species (Neuroptera: Mantispidae) from the mid-Cretaceous Burmese amber - Jouault, Corentin; Pouillon, Jean-Marc; Nel, André (Zootaxa, 2022)
A new species, namely Doratomantispa pouilloni sp. nov., of the mantidfly subfamily Doratomantispinae, is described and illustrated from a complete individual preserved in mid-Cretaceous amber from Tanai, northern Myanmar. Doratomantispa pouilloni sp. nov. preserves nearly all the diagnostic characters of this subfamily, but differs from the two other species of the genus Doratomantispa, inter alia, in its forelegs with stout trochanter, femora with nine spines on outer edge, two spines on inner edge, tibia with parallel sides, probasitarsomeres with around six pairs of black and thick spines; wings elongate and narrow, forewings with costal veinlets simple before ScP and RA fusion, coloration pattern present. Doratomantispa pouilloni sp. nov. highlights the diversity and the niche specialization of mid-Cretaceous Mantispidae from Tanai amber.